2019
DOI: 10.1111/jdv.15582
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata: a long‐term follow‐up study of 104 patients

Abstract: Background Alopecia areata (AA) is a common autoimmune disease that considerably affects the quality of life. Although several studies have investigated the epidemiology, clinical characteristics and treatment of AA, limited recent data are available regarding its long‐term course. Objectives To evaluate the long‐term course of AA in different age groups. Methods A retrospective evaluation of patients who were newly diagnosed with AA from 2008 to 2011 and had at least 7 years of follow‐up. Data regarding the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
1
27
0
2
Order By: Relevance
“…We found that disease onset at an early age and AA types with extensive hair loss were more prevalent in patients with progression than in no progression group, with similar results reported previously [10, 11]. Lyakhovitsky et al [10] found that patients with disease onset at an early age had a higher prevalence of disease severity. However, some authors have not found these associations [9] and remain controversial.…”
Section: Discussionsupporting
confidence: 91%
“…We found that disease onset at an early age and AA types with extensive hair loss were more prevalent in patients with progression than in no progression group, with similar results reported previously [10, 11]. Lyakhovitsky et al [10] found that patients with disease onset at an early age had a higher prevalence of disease severity. However, some authors have not found these associations [9] and remain controversial.…”
Section: Discussionsupporting
confidence: 91%
“…20 Instead, younger age of onset and severe hair loss on first consultation are important prognostic factors. 6,7 The median age of our patients is 62 (SD = 15;…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Classic AA is difficult to treat with high rates of relapse and will progress into permanent hair loss in a subset of patients. 6,7 It is unclear if ICI-induced AA follows a similar course. With the expanding use of ICI to treat a wide range of malignancies, the incidence of irAEs including AA will invariably increase.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, alopecia only occurred in middle-aged people, but, recently, it has been frequently occurring in individuals in their 20 and 30 seconds. [16,17] The most common type of male hair loss is androgenetic alopecia, which occurs gradually over time and most pronouncedly begins at the crown of the head and proceeds towards the forehead.…”
Section: Introductionmentioning
confidence: 99%
“…The types and causes of hair loss studied so far vary; several studies presumed that the causes of alopecia are excessive sebum production due to endocrine disorders (eg hormone imbalance), circulatory disorders (eg autonomic nervous system and blood circulation disorders), hair follicle malnutrition, allergy, bacterial infection, genetic factors, mental stress, environmental factors (eg air or food pollution) and ageing. In the past, alopecia only occurred in middle‐aged people, but, recently, it has been frequently occurring in individuals in their 20 and 30 seconds …”
Section: Introductionmentioning
confidence: 99%